Asystole During Electroconvulsive Therapy: Does Electrode Placement Matter? A Systematic Review. Issue 1 (11th March 2023) - Hartnett, Sophie; Rex, Steffen; Sienaert, Pascal
Abstract: Asystole presenting at the start of electrical stimulus application during electroconvulsive therapy (ECT) is a relatively common occurrence. It is most likely caused by vagal nerve stimulation, affecting autonomic cardiac tone. This article reviews the effect of the electrode placement (EP) on the incidence and severity of bradycardia and asystole. A systematic literature review was conducted using the Embase and PubMed databases, up to September 2021, searching for studies evaluating the effect of EP on bradycardia and/or asystole during ECT. Nine case reports describing asystole in patients receiving ECT almost exclusively reported the association with bitemporal (BT) EP. One small descriptive study found no significant effect of EP on cardiac pauses. The results from 4 cohort studies, however, suggest that a right unilateral placement bears a higher risk for developing bradycardia and asystole than BT and bifrontal ECT. The available evidence suggests that right unilateral ECT holds a greater risk for the development of bradycardia and asystole than BT and bifrontal EP.